Characterization and optimization of actuating poly(ethylene glycol) diacrylate/acrylic acid hydrogels as artificial muscles. (19th May 2017) - Browe, Daniel P.; Wood, Caroline; Sze, Matthew T.; White, Kristopher A.; Scott, Tracy; Olabisi, Ronke M.; Freeman, Joseph W.
Abstract: Large volume deficiencies in skeletal muscle tissue fail to heal with conservative treatments, and improved treatment methods are needed. Tissue engineered scaffolds for skeletal muscle need to mimic the optimal environment for muscle development by providing the proper electric, mechanical, and chemical cues. Electroactive polymers, polymers that change in size or shape in response to an electric field, may be able to provide the optimal environment for muscle growth. In this study, an electroactive polymer made from poly(ethylene glycol) diacrylate (PEGDA) and acrylic acid (AA) is characterized and optimized for movement and biocompatibility. Hydrogel sample thickness, overall polymer concentration, and the ratio of PEGDA to AA were found to significantly impact the actuation response. C2C12 mouse myoblast cells attached and proliferated on hydrogel samples with various ratios of PEGDA to AA. Future experiments will produce hydrogel samples combined with aligned guidance cues in the form of electrospun fibers to provide a favorable environment for muscle development. Graphical abstract: Highlights: A biocompatible actuator may help develop muscle tissue in vitro. An actuator made of PEGDA and acrylic acid (AA) was produced and characterized. Actuation was optimized with respect to sample geometry and composition. Despite less than optimal adhesion, cells attached and survived on PEGDA-AA slabs.